Fiqh Jihad: Upaya Mewujudkan Darul Islam antara Konsep dan Pelaksanaannya - BUTHY, Muhammad Sa'id Ramadhan al (Pustaka an-nabaa', 2001)
Fiqh Jihad: Upaya Mewujudkan Darul Islam antara Konsep dan Pelaksanaannya